Daya Tarik Selebriti Endorser Anggun C. Sasmi Pada Iklan Shampo Pantene - Shinta Hartini Putri (Universitas Informatika dan Bisnis Indonesia, 2019)
Advertising is one of the marketing activities of a company in order to promote its products. P & G initially has not been able to break through the selling of women's shampoo products. However, slowly but surely, Pantene shampoo fame has shifted its competitors through creative advertising and promo by celebrity endorsement attractiveness. The purpose of this study is to describe the attractiveness of Anggun C. Sasmi in Pantene Shampoo advertisements in the Similarity and Likability aspects. This research method uses literature study by collecting secondary data from literature studies and documents related to advertising and celebrity endorsers. The results of research in the use of celebrity endorser Anggun C. Sasmi as a form of ad appeal has reached its final goal, namely the formation of a good brand image in the minds of consumers through similarity and likability. This was further strengthened by the award given to Pantene Shampoo from several survey institutions.